Leitura e escrita na produção de uma revista no suporte digital: o gênero reportagem como objeto de aprendizagem - Matos, Nathalia Machado (2016)
Working with reading and writing in contemporary times has been one of the great challenges for the language teacher. In this perspective, the purpose of this work was to present a pedagogical proposal, in the model of a didactic sequence, for the development of discursive skills related to reading and writing activities, using as a learning object the genre reportage transmitted in digital media. The subjects who participated in the development of this didactic sequence were students from the 8th grade class of a state school network located in a city in the interior of Bahia. Considering that one of the main events that characterize the current society are the advancement and diffusion of the digital technologies, it is observed the need to integrate the new technologies to the process of teaching and learning. However, it is important to emphasize that this integration must develop consciously and critically and, above all, present a pedagogical intentionality, since the use of technology in the classroom is not justified by itself. It is based on this pressing need that, through the didactic sequence proposed in this work, it was intended to provide practices for understanding and producing texts, culminating in the creation of an online magazine, the final product of this research. For that, the genre was mobilized, since reporting is a textual activity that is part of daily life and relevant in the journalistic sphere. The methodological procedures adopted in the study take into account the qualitative approach of the research, being ethnographic and of an applied nature. The basic theoretical assumptions involved the proposal of adaptation to the model of Dolz, Noverraz and Schneuwly (2004); The theory of Bakhtin and his Circle; Studies of authors of Textual Linguistics, as well as of different theoretical frameworks that deal with the study of writing and text. The results and conclusions reached above all show that it is possible to develop a didactic sequence that allows for the practice of comprehension and production of texts and the use of digital technologies as an instrument for acquiring information and for socializing the knowledge produced.